Workshop Guru Dalam Peningkatan Pengelolaan Kelas Pada Proses Pembelajaran Smk Arrasyadiyah Kota Serang - Marliani, Novi; Farabi, M. Nur El; Rusmana, Indra Martha (Universitas Indraprasta PGRI, 2025)
Effective classroom management is a crucial factor in creating a conducive and enjoyable learning environment, which positively influences student’s motivation, participation, and academic performance. Based on observations at SMK Arrasyaddiyah in Serang City, several challenges were identified, including low student engagement, lack of varied teaching methods, minimal use of technology, and limited teacher training. To address these issues, the community service team from Universitas Indraprasta PGRI conducted a workshop on enhancing classroom management competence, aimed at equipping teachers with innovative and technology-based classroom management strategies. The program was implemented over a four-month period (April–August) in the form of interactive workshop, including lectures, group discussions, classroom management simulations and evaluation pre- and post-tests. The results of showed an improvement in teachers' knowledge and skills in class management, as well as high enthusiasm toward the training content. Teachers demonstrated greater ability in time management, student interaction, and the application of engaging learning methods tailored to student’s learning styles. Thus, this program has made a tangible contribution to improving and served as one of the solutions for strengthening technology-based and collaborative classroom management in vocational high schools.